The Relationships between Parental Involvement, Students’ Basic Psychological Needs and Students’ Engagement in Science: A Path Analysis - Uluhan Kurt; Yasemin Tas (Journal of Education in Science, Environment and Health)
This study aimed to investigate relationships between Turkish middle school students’ perceptions of parental involvement, students’ basic psychological needs, and their engagement in science. Parental involvement was addressed with four dimensions: parents’ educational aspiration, parental communication, parents’ participation, and parental autonomy support. Students’ basic psychological needs incorporated autonomy, competence, and relatedness. Additionally, students’ engagement consisted of behavioral, cognitive, emotional, and agentic engagement. The sample of the study included 926 sixth, seventh, and eight grade students educated in one of the largest cities located in eastern part of Turkey. A path analysis using LISREL 8.8 programme was conducted to examine the hypothesized relations among variables of the study. Analysis results showed that parent educational aspiration, parental communication, parent participation, and parent autonomy support were statistically significantly and positively related to basic psychological needs. Besides, students whose basic psychological needs were met demonstrated more behavioral, cognitive, emotional, and agentic engagement in science.